A Historical Review of Educational Curriculum Development in Indonesia - Siti Safura (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This article presents a historical review of the development of the education curriculum in Indonesia, from the colonial era to contemporary reforms. The discussion highlights major curriculum changes that have shaped the national education system, beginning with post-independence curricula and continuing through reforms designed to respond to political, social, and economic developments. The 1947 Curriculum and the 1968 Curriculum are identified as important milestones in strengthening national identity, promoting unity, and supporting national development goals. The article also explains how global educational paradigms and local socio-cultural contexts have influenced curriculum design in Indonesia. These influences are reflected in the growing emphasis on character education, critical thinking skills, vocational competencies, and the holistic development of students. Recent curriculum reforms, such as the 2013 Curriculum and the Merdeka Curriculum, aim to create more student-centered learning, provide greater flexibility in the learning process, encourage independent learning, and support the development of 21st-century skills. However, the implementation of these reforms continues to face several challenges, including regional disparities, unequal access to educational resources, and limitations in teacher readiness and professional development. These issues affect the effectiveness of curriculum implementation across various educational contexts in Indonesia. The article concludes that future curriculum development should prioritize inclusiveness, adaptability, sustainability, and technological integration to address the evolving demands of society and improve the quality of national education.